Analisis Strategi Coping Stres pada Ibu Single Parent Setelah Ditinggal Suami: Literatur Sistematik Review - Dulce Elda Ximenes Dos Reis; Endang Retno Surjaningrum; Ike Herdiana (Mahesa Research Center, 2021)
The purpose of this literature is to determine the selection of stress coping strategies used by single parent mothers in dealing with problems after the abandonment of their husbands. The method used in writing this literature review is to search for literatures using databases such as http://garuda.ristekbrin.go.id/ and Google Scholar. The results of this literature review identified five articles that met the inclusion criteria. From the literature obtained, the majority use this type of qualitative research as many as 3 articles and 2 articles using quantitative research. Several studies have shown that the most effective and often used strategies for single parent mothers after their husband leave behind are problem focused coping and emotion focused coping.The conclusion of the study shows that the situations that cause stress to the three single parent mothers after the abandonment of their husbands are (a) the dual roles that are played after the husband leaves, namely meeting the psychological needs of the child, (b) work, (c) accusations from neighbors and (d) economic problems. The coping strategies used by single parents after their husband left their husbands are emotional focused coping (coping that focuses on emotions) and problem focused coping (coping that focuses on problems). Emotional focused coping that is used is avoiding problems, ignoring problems, blaming yourself and interpreting problems. Meanwhile, the problem focused coping used is exercised caution, instrumental action and negotiation.